A CRITICAL ANALYSIS OF SEOJK NUMBER 10/SEOJK.04/2025: BALANCING TRANSPARENCY AND EFFICIENCY IN THE INDONESIAN CAPITAL MARKET - Michael H. Hadylaya (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines Financial Services Authority Circular Letter No. 10/SEOJK.04/2025 on Electronic Reporting of Share Ownership and Underwriting Activities by Public Companies (SEOJK 10/2025), with a focus on its alignment with the principle of information transparency and its implications for regulatory effectiveness. Using a normative legal research approach supported by policy analysis and comparative references, the study finds that while the regulation strengthens the formal structure of disclosure in Indonesia’s capital market, its current design may raise proportionality concerns and affect investor protection. Without adequate flexibility, such as deferral mechanisms or differentiated reporting channels, the policy risks generating excessive compliance burdens and unintended strategic disclosures. The study recommends adopting a two-tier reporting system and risk-based exceptions to preserve regulatory legitimacy while protecting market integrity.